Struggling for change: provision for the professional development of foreign language teachers of young learners in Bydgoszcz, Poland - Wiśniewska, Sylwia (2005)
Due to economic and political changes in Poland the market for educational services has changed. A worldwide trend for an early start in foreign language (FL) instruction is reflected in the accelerated growth of numbers of younger children enrolled into various forms of FL learning in Poland. Recent changes in the new National Curriculum introduced the possibility of starting FL learning from the first grade of the elementary school. However, it seems that teacher training has not yet responded to the growing demand for qualified FL teachers of young learners (FLTYL).